Cross-Reactivity of Guillain-Barre Syndrome and Thrombotic Thrombocytopenic Purpura with Complications Respiratory Failure: Case Report - Harlasgunawan, Alia Rahmi; Palo, Daud; Abdullah, Dirman; Priambodo, Ayu Prawesti; Mirwanti, Ristina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Guillain-Barre Syndrome (GBS) and Thrombotic Thrombocytopenic Purpura (TTP) are two medical conditions that are rare but can cause serious complications if they appear simultaneously. Both conditions involve autoimmune mechanisms and can result in organ failure, including respiratory failure. Although there are several case reports of each condition, research exploring the interaction between GBS and TTP in the context of respiratory failure is limited. Purpose: The aim of this study is to describe a case of cross-reactivity of Guillian-Barre Syndrome and Thrombotic Thrombocytopenic Purpura with complications respiratory failure. Methods: This research uses a case study design involving an adult patient who was treated at a hospital in Bandung. Data was collected through a comprehensive nursing assessment. Patients provided informed consent before data were collected. Data analysis was carried out descriptively to describe clinical findings and patient management results. Results: The patient is a young woman 27 year old admitted to hospital with a diagnosis of GBS. Eleven days before entering the hospital the patient experience dascending paralysis, fever, nausea and vomiting.TTP cross-reactivity and peripheral nervous system inflammation in GBS.Complications of respiratory failure requiring invasive mechanical ventilation (IMV) in the ICU. Laboratory and radiological examinations supported the diagnosis, and medical intervention was performed according to protocol for both conditions. This shows the importance of close monitoring and prompt treatment to prevent further complications. These findings emphasize the need for a multidisciplinary approach in managing patients with complex medical conditions. Conclusion: An in-depth understanding of the interaction between GBS and TTP is essential for effective clinical management, especially in preventing and managing complications of respiratory failure.